Use of oil-in-water emulsions to control fungal deterioration of strawberry jams. (15th November 2016) - Ribes, Susana; Fuentes, Ana; Talens, Pau; Barat, José M.
Highlights: The antifungal potential of essential oils and their emulsions has been evaluated. Clove and cinnamon leaf essential oils have shown the highest antifungal activity. Oil and polymer contents were established by physico-chemical and in vitro tests. Oil-in-water emulsions were able to prevent mould growth in strawberry jams. Abstract: This work aimed to control the fungal deterioration of strawberry jams. The antifungal activity of the clove, cinnamon leaf, lemon and mandarin essential oils and their effectiveness in oil-in-water emulsions were evaluated. According to the results obtained, only clove and cinnamon leaf oils were selected to prepare emulsions. All the tested emulsions were stable, independently the amount of polymer and essential oil used. Essential oil loss was affected by the amount of polymer employed to prepare the emulsions. The oil-in-water emulsions with 5.0 mg/g xanthan gum, and with 0.55 mg/g clove or 0.65 mg/g cinnamon leaf essential oil, were used for the in vivo tests. The jams prepared with the oil-in-water emulsions showed a lower fungal decay compared with jams without emulsion. The present work demonstrated that emulsions can be employed to prevent strawberry jam mould spoilage.